The Influence Costumer Cognitif Factor on Brand Equity Through Brand Personality - Riyanto, Fery; GS, Achmad Daengs; Panjaitan, Roymon; Yusuf, Muhammad; Sukri, Saipul Al (Politeknik APP Jakarta, 2023)
The purpose of this study is to analyze the influence of consumer cognitive factors such as brand association, perceived quality of the brand, brand image, and brand reputation on brand equity both directly and indirectly via brand personality. This type of study is explanatory. This study used a purposive sampling method and included 100 Shopee users as respondents from Kebumen and the nearby districts. Data analysis was performed descriptively, and path analysis. The results of this studied indicate that cognitive factors partially; brand association and brand reputation have a significant impact effect on brand personality, brand image and perceived quality of brand did not affect brand personality, perceived quality of brand, brand image and brand personality have positive effect on brand equity. Brand personality is proven to be able to mediate brand association and brand reputation towards brand equity. The perceived quality of brand and brand image are proven not to be mediated by brand personality.